Pengaruh Kosakata dan Tata Bahasa terhadap Kemampuan Menulis Teks Deskripsi (International Forum of Researchers and Lecturers, 2025)
The purpose of this study was to determine the use of vocabulary on the ability to write descriptive texts, to find out grammar on the ability to write descriptive texts and to find out the relationship between the use of vocabulary and grammar on the ability to write descriptive texts in students of SMP Negeri 11 Jayapura City. With a quantitative research method. Based on the analysis that has been done, it can be concluded that there is a significant influence of vocabulary and grammar mastery on the ability to write descriptive texts of junior high school students in Jayapura City. statistically proven with a significant value (Sig.) which is smaller than 0.05 on all variables tested, both individually and together. These results indicate that the combination of vocabulary and grammar mastery is very important to improve students' descriptive text writing skills. Overall, the variables of grammar and vocabulary mastery can explain 60 percent of the variation in students' descriptive text writing skills, with vocabulary making a greater contribution (35.74 percent) than grammar (24.26 percent). These findings emphasize the importance of focusing on developing vocabulary and grammar simultaneously to achieve the best results in learning to write descriptive texts in junior high schools in Jayapura City.